PEMIKIRAN MAZHAB FIQH IMAM SYAFI’I - Fahrur Rozi (JURNAL HAKAM, 2021)
The leadership of fiqh in Medina culminated in Imam Malik, and Imam Shafi'I went to Medina to study with him. And when the leadership of fiqh in Iraq culminated in Abu Hanifah, he studied fiqh in Iraq from Muhammad ibn al-Hasan al-Syaibany (one of Abu Hanifah's students). Therefore, Imam Shafi'i gathered knowledge of fiqh Ashab al-Ra'yi (Imam Malik) and fiqh Ashab al-Ra'yi (Abu Hanifah). The religious sect of Imam Shafi'i, as well as other schools of thought from the priests of the four schools: Abu Hanifah, Malik bin Anas, and Ahmad ibn Hanbal, are members of the Ahlu al-Sunnah wa al-Jama'ah group. Ahlu al-Sunnah wa al-Jama'ah in the field of furu' is divided into two schools, namely the Ahlu al-Hadith school and the Ahlu al-Ra'yi school. Imam Shafi'i, including Ahlu al-Hadith. Imam Shafi'i was famous for defending the Maliki school and defending the Medina school of thought until he was known as Nasyirus Sunnah (spreader of the Sunnah). This is the result of bringing together the fiqh of Medina and the fiqh of Iraq. Qaul Qadim (as the result of the first ijtihad) and qaul Jadid (as the first legal decision changer) of Imam Shafi'i was revealed in several issues.